Stability Analysis of Irregular Cavities in Tunnel Using Geomagic-COMSOL Coupling Method - Shangqu Sun; Chengshuai Qin; Hongbo Wang; Liping Li; Yongliang Huang (Advances in Civil Engineering)
The erosion of soluble rock and transformation of groundwater result in the high irregularity of cavities in tunnel. At present, however, karst cavities are mainly simplified as circular, rectangular, or elliptical shape in the numerical simulation. The purpose of this paper is to propose a new method to analyze the stability of irregular cavities. First of all, we used the drilling laser scanning method to reconstruct the three-dimensional point clouds model of irregular cavities. Furthermore, we proposed the method of determining the point density to reduce the computational error under the premise of ensuring the accuracy in engineering scale. We also developed the Geomagic-COMSOL coupling numerical method to conduct the stability analysis of irregular cavities. The results demonstrated that the geometrical shape of karst cavities has great effects on the deformation and mechanical properties of the surrounding rock. The displacement and equivalent plastic strain of simplified cavities exhibited symmetric characteristics, while those of irregular cavities are highly randomly distributed. We noted that a greater displacement value and more intensive plastic strain can be triggered by irregular cavities shape, compared with the simplified cavity shape. The results also showed that the larger displacement occurred at the long-edge part, while the plastic zone was concentrated at the sharp turning angle of the irregular cavities.